Involvement of hydrogen sulfide in the progression of renal fibrosis - Wang, Yu (Chin Med J (Engl), 2019)
OBJECTIVE: Renal fibrosis is the most common manifestation of chronic kidney disease (CKD). Noting that existing treatments of renal fibrosis only slow disease progression but do not cure it, there is an urgent need to identify novel therapies. Hydrogen sulfide (H(2)S) is a newly discovered endogenous small gas signaling molecule exerting a wide range of biologic actions in our body. This review illustrates recent experimental findings on the mechanisms underlying the therapeutic effects of H(2)S against renal fibrosis and highlights its potential in future clinical application. DATA SOURCES: Literature was collected from PubMed until February 2019, using the search terms including “Hydrogen sulfide,” “Chronic kidney disease,” “Renal interstitial fibrosis,” “Kidney disease,” “Inflammation factor,” “Oxidative stress,” “Epithelial-to-mesenchymal transition,” “H(2)S donor,” “Hypertensive kidney dysfunction,” “Myofibroblasts,” “Vascular remodeling,” “transforming growth factor (TGF)-beta/Smads signaling,” and “Sulfate potassium channels.” STUDY SELECTION: Literature was mainly derived from English articles or articles that could be obtained with English abstracts. Article type was not limited. References were also identified from the bibliographies of identified articles and the authors’ files. RESULTS: The experimental data confirmed that H(2)S is widely involved in various renal pathologies by suppressing inflammation and oxidative stress, inhibiting the activation of fibrosis-related cells and their cytokine expression, ameliorating vascular remodeling and high blood pressure, stimulating tubular cell regeneration, as well as reducing apoptosis, autophagy, and hypertrophy. Therefore, H(2)S represents an alternative or additional therapeutic approach for renal fibrosis. CONCLUSIONS: We postulate that H(2)S may delay the occurrence and progress of renal fibrosis, thus protecting renal function. Further experiments are required to explore the precise role of H(2)S in renal fibrosis and its application in clinical treatment.